Coating material

By adding a compound with a specific acid value to the coating material, the challenges of balancing pot life and crack resistance in forming thick films are addressed, resulting in a coating material that ensures sufficient usable time and prevents cracking.

JP2025069071APending Publication Date: 2025-04-30F CONSULTANT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024174746
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-17
Filing Date
2024-10-04
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing coating materials struggle to balance pot life and crack resistance when forming thick films, especially in environments with varying temperatures.

Method used

Incorporating a compound with a specific acid value of 10 to 1000 mgKOH/g into the coating material, which includes a polyol component, a polyisocyanate component, and a powder component, to enhance pot life and prevent cracking.

Benefits of technology

The coating material achieves sufficient pot life and forms thick films without cracking, even under high temperature conditions, while maintaining excellent physical properties and appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069071000001
    Figure 2025069071000001
  • Figure 2025069071000002
    Figure 2025069071000002
Patent Text Reader

Abstract

To provide a coating material that can secure a sufficient usable time (pot life) of the coating material and that enables formation of a thick film without causing problems such as cracking.SOLUTION: A coating material comprises a film-forming component (A) and a powder component (B), wherein the film-forming component (A) comprises a polyol component (A1) and a polyisocyanate component (A2), and wherein the powder component (B) is contained in an amount of 100 pts.mass or more based on 100 pts.mass of solid content of the film-forming component (A), and the coating material further comprises a compound (C) having an acid value of 10 to 1000 mgKOH / g.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel coating material. [Background technology]

[0002] Conventionally, urethane coating materials consisting of polyol and polyisocyanate components have been used in a wide range of applications, such as anticorrosive paints, fireproof paints, waterproof paints, floor paints (flooring materials), sealants, and paving materials. These coating materials may form thick films to enhance their properties. To form a thick film, the coating material must be applied multiple times, which poses the problem of a long construction period. On the other hand, coating materials that can form thick films with a single coat have also been developed. For example, Patent Document 1 describes a two-liquid coating composition that uses a vinyl resin of a specific molecular weight and a hydroxyl group-containing resin in combination, and that can be made high solid by mixing a composition containing a catalyst and a polyisocyanate compound immediately before use. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-109753 A Summary of the Invention [Problem to be solved by the invention]

[0004] In the case of high-solid paints containing a large amount of resin components, such as those in Patent Document 1, thicker films can be produced by increasing the reactivity of the resin through the addition of an appropriate amount of catalyst. However, in coating materials that contain a small amount of resin components and a large amount of powder components such as pigments and fillers, for example, when a catalyst is added to enhance the reactivity of the resin, it may not be possible to ensure a sufficient pot life. In particular, in high temperature environments, this may lead to a decrease in coating workability and a risk of impairing the appearance and physical properties of the formed coating. On the other hand, when trying to secure a pot life, the reactivity of the resin decreases, and cracks may occur when forming a thick film. In particular, in a low temperature to room temperature environment, if the reactivity of the resin decreases, it becomes difficult to form a thick film. In this way, it is difficult to achieve both pot life and crack resistance when forming a thick film, and there is room for improvement.

[0005] The present invention has been made in consideration of such problems, and has an object to provide a coating material that can ensure a sufficient pot life of the coating material and that can form a thick film without causing defects such as cracks. [Means for solving the problem]

[0006] In order to solve these problems, the present inventors discovered that by including a compound having a specific acid value in a coating material, the usable time (pot life) of the coating material can be sufficiently ensured and furthermore, a thick film can be formed without causing defects such as cracking, thereby completing the present invention.

[0007] That is, the present invention has the following features. 1. A coating material comprising a film-forming component (A) and a powder component (B), The film-forming component (A) comprises a polyol component (A1) and a polyisocyanate component (A2), The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The coating material further comprises a compound (C) having an acid value of 10 to 1000 mgKOH / g. 2. A multi-component coating material having a base material containing a polyol component (A1) and a powder component (B) and a curing agent containing a polyisocyanate component (A2), the polyol component (A1) and the polyisocyanate component (A2) are a film-forming component (A); The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The multi-component coating material is characterized in that the main component contains a compound (C) having an acid value of 10 to 1000 mgKOH / g. Effect of the Invention

[0008] The present invention relates to a coating material that contains, as a film-forming component (A), a polyol component (A1) and a polyisocyanate component (A2), and further contains a powder component (B). By further containing a compound (C) having a specific acid value, the usable time (pot life) of the coating material can be sufficiently ensured, and furthermore, a thick film can be formed without causing defects such as cracks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below based on the embodiments.

[0010] The coating material of the present invention contains a polyol component (A1) and a polyisocyanate component (A2) as a coating-forming component (A). The polyol component (A) and the polyisocyanate (A2) are components that react to form a coating. The polyol component (A1) and the polyisocyanate component (A2) are liquid at room temperature (25°C) and may be either a solventless type or a solvent type.

[0011] In the present invention, examples of the polyol component (A1) include polyester polyols, polyether polyols, polycarbonate polyols, polylactone polyols, polybutadiene polyols, polypentadiene polyols, castor oil, castor oil-based polyols, fluorine-containing polyols, acrylic polyols, etc. These are appropriately selected and used depending on the application of the coating material (for example, anticorrosive paints, fireproof paints, waterproof paints, floor paints (flooring materials), sealing materials, paving materials, putty materials, etc.), and one or more types can be used.

[0012] Examples of the polyester polyol include aromatic polyester polyol, aliphatic polyester polyol, and aromatic / aliphatic polyester polyol.

[0013] Specifically, the aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting a saturated aliphatic polybasic acid such as succinic acid, adipic acid, azelaic acid, or sebacic acid with a polyhydric alcohol, and condensation polyester polyols obtained by reacting an unsaturated aliphatic polybasic acid such as maleic acid or fumaric acid with a polyhydric alcohol.

[0014] The aromatic polyester polyol is a polyol having an aromatic hydrocarbon in one molecule, and examples thereof include condensed polyester polyols obtained by reacting an aromatic polybasic acid such as orthophthalic acid, isophthalic acid, terephthalic acid, phthalic anhydride, etc. with a polyhydric alcohol, and phthalic acid-based polyester polyols obtained by decomposing a phthalic acid-based polyester molded product such as polyethylene terephthalate, etc. In addition, examples of the polyhydric alcohol include dihydric or higher alcohols and derivatives thereof, dihydric or higher phenols, polyols, etc.

[0015] The aromatic / aliphatic polyester polyol is a polyol having an aliphatic hydrocarbon and an aromatic hydrocarbon in one molecule, and examples thereof include condensation polyester polyols obtained by reacting an aromatic polybasic acid or an aliphatic polybasic acid with a polyhydric alcohol.

[0016] Examples of the polyether polyol include aromatic polyether polyols, phosphorus-containing polyether polyols, glycerin-based polyether polyols, and amino group-containing polyether polyols.

[0017] Examples of the aromatic polyether polyol include bisphenol A-type polyether polyols obtained by adding an alkylene oxide (e.g., ethylene oxide, propylene oxide, etc.) to bisphenol A as an initiator, and aromatic amine-based polyether polyols obtained by adding an alkylene oxide to an aromatic amine (e.g., toluenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, p-phenylenediamine, o-phenylenediamine, naphthalenediamine, triethanolamine, Mannich condensation products, etc.) as an initiator.

[0018] Examples of the phosphorus-containing polyether polyol include dialkyl-N,N-bis(2-hydroxyethyl)aminomethylphosphonate, which is a diol having a phosphoric acid ester structure.

[0019] The glycerin-based polyether polyols include polyether polyols obtained by adding alkylene oxide to glycerin as an initiator.

[0020] Examples of the amino group-containing polyether polyol include those obtained by adding an alkylene oxide to a low molecular weight amine (for example, ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, neopentyldiamine, etc.) as an initiator.

[0021] The castor oil-based polyol is a polymer derived from castor oil or castor oil fatty acid, and examples thereof include alkylene oxide adducts of castor oil or castor oil fatty acid, epoxidized products of castor oil or castor oil fatty acid, halides of castor oil or castor oil fatty acid, transesterification products of castor oil or castor oil fatty acid and polyhydric alcohol, and hydrogenated products thereof.

[0022] The fluorine-containing polyol may be a copolymer of a fluorine-containing monomer, such as a fluoroolefin monomer or a fluoroalkyl group-containing acrylic monomer, a hydroxyl group-containing vinyl monomer, and, if necessary, another polymerizable monomer.

[0023] The polyol component (A1) is selected depending on the intended use of the coating material. For example, in the case of a fire-resistant coating material, it is preferable that the polyol component (A1) contains a polyether polyol. The content of the polyether polyol is preferably 50 mass% or more (more preferably 60 to 100 mass%, and even more preferably 70 to 98 mass%) based on the total amount of the polyol component (A1). In the present invention, "α to β" is synonymous with "α or more and β or less".

[0024] The hydroxyl value of the polyol (A1) is not particularly limited, but is preferably 3 to 150 mgKOH / g, more preferably 5 to 100 mgKOH / g, even more preferably 7 to 40 mgKOH / g, and most preferably 10 to 30 mgKOH / g. For example, in the case of a fire-resistant paint, such a hydroxyl value is advantageous in terms of improving physical properties. In the present invention, the hydroxyl value is a value (mgKOH / g) represented by the number of mg of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of solid content.

[0025] The molecular weight of the polyol component (A1) is not particularly limited, but is preferably 5000 or more (more preferably 6000 to 20000). For example, in the case of a fire-resistant paint, by using such a polyol component (A1), the temperature of the coating film is increased (preferably the surface temperature of the coating film is 200°C or more, more preferably 250°C or more), and excellent foaming properties are exhibited, thereby improving the fire resistance of the substrate. In the present invention, the molecular weight of the polyol component is a number average molecular weight (Mn), which is a so-called polystyrene-equivalent molecular weight determined by gel permeation chromatography using a polystyrene polymer as a reference.

[0026] Furthermore, the polyol component (A1) of the present invention may have an acid value, but the acid value is preferably less than 10 mgKOH / g (more preferably 8 mgKOH / g or less, and even more preferably 5 mgKOH / g or less), and is different from the compound (C) having an acid value described below. In the present invention, a polyol component having an acid value of 10 mgKOH / g or more is classified as a component corresponding to the compound (C) having an acid value described below. In the present invention, the acid value is a value (mgKOH / g) represented by the number of mg of potassium hydroxide equivalent to the moles of acid groups contained in 1 g of solid content.

[0027] The polyisocyanate component (A2) of the present invention has two or more isocyanate groups in one molecule and reacts with the polyol to form a coating film, and various known isocyanates can be used.

[0028] Examples of the polyisocyanate component include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, etc., and derivatives thereof by allophanation, biuretization, dimerization (uretidione), trimerization (isocyanurate), adductation, carbodiimide reaction, etc., mixtures thereof, and copolymers thereof with monomers copolymerizable therewith, etc. These can be used alone or in combination of two or more.

[0029] Examples of the aliphatic diisocyanate include 1,3-trimethylene diisocyanate, 1,4-tetramethylene diisocyanate, 1,3-pentamethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HMDI), 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, and 1,3-butylene diisocyanate. anate, 2-methyl-1,5-pentamethylene diisocyanate, 3-methyl-1,5-pentamethylene diisocyanate, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, lysine diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.

[0030] Examples of the alicyclic diisocyanate include 1,3-cyclopentane diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, 1,4-bis(isocyanatomethyl)cyclohexane, isophorone diisocyanate (IPDI), norbornane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, and hydrogenated xylylene diisocyanate.

[0031] Examples of the aromatic diisocyanate include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate (TDI), 2,6-tolylene diisocyanate (TDI), naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 4,4'-diphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 2,4'-diphenylmethane diisocyanate, Examples of the isocyanate include 4,4'-diphenyl ether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylene xylylene diisocyanate.

[0032] Examples of the aromatic aliphatic diisocyanate include 1,3-xylylene diisocyanate (XDI), 1,4-xylylene diisocyanate (XDI), ω,ω'-diisocyanate-1,4-diethylbenzene, 1,3-bis(1-isocyanate-1-methylethyl)benzene, 1,4-bis(1-isocyanate-1-methylethyl)benzene, and 1,3-bis(α,α-dimethylisocyanate methyl)benzene.

[0033] In the present invention, it is particularly preferable to contain an aliphatic diisocyanate such as HMDI and its derivatives. The content of the aliphatic diisocyanate is preferably 90% by mass or more (more preferably 95% by mass or more) based on the total amount of the polyisocyanate component (A2).

[0034] The polyol component (A1) and the polyisocyanate component (A2) are mixed in such a ratio that the NCO / OH equivalent ratio of the polyol component (A1) and the polyisocyanate component (A2) is preferably 0.6 to 3.5 (more preferably 1 to 3.0, and even more preferably 1.1 to 2.5). In such a case, a coating film having excellent curability and a uniform thickness of a desired thickness can be formed. Furthermore, the formed coating film has excellent durability (e.g., waterproofness, water impermeability, crack resistance, conformability to substrate, etc.) and can maintain the initial appearance (beauty) for a long period of time.

[0035] In the present invention, a curing catalyst (P) that promotes the reaction between the polyol component (A1) and the polyisocyanate component (A2) can be used in combination. The curing catalyst (P) is a substance that promotes the reaction of isocyanate groups to cause curing. Examples of the curing catalyst (P) include various types of amine catalysts, organometallic catalysts, and inorganic catalysts. Examples of amine catalysts include ethylenediamine, triethylenediamine, triethylamine, ethanolamine, diethanolamine, and hexamethylenediamine, or derivatives thereof, or mixtures thereof with solvents. Examples of organometallic catalysts include organometallic compounds such as dibutyltin dilaurate and dibutyltin diacetate; and organometallic salts such as potassium acetate, zinc stearate, calcium stearate, lead stearate, aluminum stearate, and tin octylate. Examples of inorganic catalysts include tin chloride. These can be used alone or in combination, and can also be used by mixing with a solvent. In the present invention, it is particularly preferable to contain an organometallic catalyst (most preferably dibutyltin dilaurate or dibutyltin diacetate), which can accelerate curing and further enhance the curability of the film-forming component.

[0036] The amount of the curing catalyst (P) is preferably 0.05 to 3 parts by mass (more preferably 0.08 to 2.8 parts by mass, and even more preferably 0.1 to 2.5 parts by mass) of the active ingredient per 100 parts by mass of the solid content of the film-forming component (A). In this case, the crosslinking reaction of the film-forming component (A) can be sufficiently promoted. The amount of the curing catalyst (P) can be set according to the coating environment.

[0037] The coating material of the present invention is characterized in that it contains a powder component (B) and contains 100 parts by mass or more (preferably 100 to 1000 parts by mass, and more preferably 150 to 800 parts by mass) of the powder component (B) per 100 parts by mass of the solid content of the coating-forming component (A). The powder component (B) is blended according to the application of the coating material (for example, anticorrosive paint, fireproof paint, waterproof paint, floor paint (floor material), sealing material, paving material, putty material, etc.), and known powders can be used. As such powder component (B), for example, one or more types selected from various pigments (coloring pigments, extender pigments, functional pigments, etc.), fibers, functionality-imparting powders, etc. can be used. The powder component (B) is in powder form (solid) at room temperature (25°C) and disperses in the coating material.

[0038] Examples of the pigment include inorganic color pigments such as titanium oxide, zinc oxide, carbon black, ferric oxide (red oxide), molybdate orange, yellow iron oxide, ultramarine, cobalt green, iron-chromium composite oxide, manganese-bismuth composite oxide, manganese-yttrium composite oxide, and manganese-iron-cobalt composite oxide; organic color pigments such as azo, naphthol, pyrazolone, anthraquinone, perylene, quinacridone, disazo, isoindolinone, benzimidazole, phthalocyanine, and quinophthalone; functional pigments such as pearl pigments, fluorescent pigments, phosphorescent pigments, metallic pigments, and rust-preventive pigments; and extender pigments (fillers) such as heavy calcium carbonate, precipitated calcium carbonate, kaolin, talc, clay, china clay, china clay, barium sulfate, barium carbonate, silica powder, and diatomaceous earth. These can be used alone or in combination of two or more.

[0039] Examples of the fibers include organic fibers such as acrylic fibers, acetate fibers, aramid fibers, cuprammonium fibers (cupra), nylon fibers, novoloid fibers, pulp fibers, viscose rayon, vinylidene fibers, polyester fibers, polyethylene fibers, polyvinyl chloride fibers, polychlar fibers, boronosic fibers, polypropylene fibers, and cellulose fibers, and inorganic fibers such as carbon fibers, rock wool fibers, glass fibers, silica fibers, alumina fibers, silica-alumina fibers, slag wool fibers, ceramic fibers, carbon fibers, and silicon carbide fibers. These can be used alone or in combination of two or more.

[0040] In the case of a fire-resistant coating, examples of the functionality-imparting powder include a foaming agent, a carbonizing agent, and a flame retardant, etc. These are components that form a carbonized heat insulating layer by interacting with the film-forming component (A) (e.g., at least one of a dehydration and cooling effect, a non-flammable gas generating effect, a carbonization promotion effect, a carbonized heat insulating layer forming effect, etc.), and can impart fire resistance.

[0041] The foaming agent imparts foaming action to the coating when the temperature rises during a fire or the like (for example, when the coating temperature reaches 200°C or higher). Examples of foaming agents include melamine and its derivatives, dicyandiamide and its derivatives, azobistetrazole and its derivatives, azodicarbonamide, urea, thiourea, etc. These can be used alone or in combination of two or more.

[0042] The carbonizing agent is a material that imparts the effect of forming a carbonized heat insulating layer by carbonizing the film-forming component (A) and dehydrating and carbonizing it due to a temperature rise during a fire, etc. Examples of the carbonizing agent include pentaerythritol, dipentaerythritol, trimethylolpropane, starch, casein, etc. These can be used alone or in combination of two or more.

[0043] Examples of the flame retardant include organic phosphorus compounds, chlorine compounds, antimony compounds, phosphorus compounds, boric acid compounds, metal hydrates, etc. As the flame retardant, particularly phosphorus compounds are suitable, and examples thereof include ammonium phosphate, ammonium polyphosphate, melamine-coated ammonium polyphosphate, melamine phosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, boron phosphate, boron polyphosphate, aluminum phosphate, aluminum polyphosphate, etc. These can be used alone or in combination of two or more.

[0044] As an example of the coating material of the present invention, the fireproof paint preferably contains functional powders such as a foaming agent, a carbonizing agent, and a flame retardant as the powder component (B), and further contains a pigment, etc. The mixing ratio is preferably 5 to 500 parts by mass (more preferably 10 to 200 parts by mass, and even more preferably 30 to 150 parts by mass) of the foaming agent, preferably 5 to 600 parts by mass (more preferably 20 to 300 parts by mass, and even more preferably 40 to 150 parts by mass) of the carbonizing agent, and preferably 50 to 1000 parts by mass (more preferably 100 to 800 parts by mass, and even more preferably 150 to 600 parts by mass) of the flame retardant, relative to 100 parts by mass of the solid content of the film-forming component (A). When a pigment is contained, the pigment is preferably contained in an amount of 10 to 300 parts by mass (more preferably 20 to 250 parts by mass, and even more preferably 30 to 160 parts by mass) per 100 parts by mass of the solid content of the coating film forming component (A).

[0045] Furthermore, the coating material of the present invention is characterized by containing a compound (C) (hereinafter, also referred to as "compound (C)") having an acid value of 10 to 1000 mgKOH / g. Note that compound (C) is liquid at room temperature (25°C) and may be either a solventless type or a solvent type. By including such a compound (C), the usable time (pot life) of the coating material is sufficiently ensured, and a thick film can be formed without problems such as cracking. Although the mechanism of action is not limited, compound (C) has the effect of primarily masking the isocyanate groups of polyisocyanate component (A2) in the coating material by blending compound (C). This reduces the reactivity of the isocyanate groups (NCO groups) of polyisocyanate component (A2), and the usable time (pot life) can be extended. In addition, in the coating material of the present invention, the NCO group of the polyisocyanate component (A2) may undergo a reaction with the OH group of the polyol component (A1) to form a urethane bond (resinification reaction), and may also undergo a reaction with moisture (humidity, etc.) in the air to generate carbon dioxide and form a urea bond (foaming reaction). In the present invention, the above-mentioned masking action can efficiently suppress the reaction with water (foaming reaction). As a result, it is presumed that the reaction with the polyol component (A1) (resinification reaction) can be sufficiently advanced, and therefore a thick film can be formed without cracking or the like. Furthermore, even in the case of the present invention in which a large amount of powder component (B) is contained relative to the coating-forming component (A) (resin component), the inclusion of compound (C) ensures a sufficient pot life, thereby making it possible to improve workability and the appearance and physical properties of the coating that is formed. Such an effect is exhibited even when a curing catalyst (P) is blended into the coating material. Therefore, it is possible to blend an optimum amount of the curing catalyst (P) into the coating material of the present invention in order to promote the resinification reaction. This makes it possible to form a thick film without causing cracks or the like while ensuring a sufficient pot life, thereby improving the appearance and physical properties of the formed coating.

[0046] The acid value of the compound (C) is 10 to 1000 mgKOH / g (preferably 12 to 800 mgKOH / g, and more preferably 15 to 600 mgKOH / g). In this case, the above-mentioned effects can be sufficiently exhibited.

[0047] Such a compound (C) is not particularly limited as long as it is a compound having the above-mentioned acid value, but is preferably at least one selected from, for example, a phosphate compound, a carboxylic acid compound, a carboxylic acid anhydride compound, a copolymer having a carboxyl group, and the like.

[0048] Examples of the phosphate ester compound include phosphate ester compounds of polyester / polyether polymers, phosphate ester compounds of polyether polymers, free acids of alkyl phosphate ester compounds, and free acids of alkyl / aryl phosphate ester compounds.

[0049] Examples of the carboxylic acid compound include fatty acids such as saturated fatty acids and unsaturated fatty acids, and derivatives of these fatty acids. Examples of saturated fatty acids include capric acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, and melissic acid. Examples of unsaturated fatty acids include decenoic acid, myristoleic acid, palmitreic acid, oleic acid, linoleic acid, linolenic acid, ricinoleic acid, paulownia oil fatty acid, linseed oil fatty acid, castor oil fatty acid, tall oil fatty acid, cottonseed oil fatty acid, soybean oil fatty acid, olive oil fatty acid, safflower oil fatty acid, and rice bran oil fatty acid.

[0050] Examples of fatty acid derivatives include hydroxy lauric acids such as 2-hydroxylauric acid and 3-hydroxylauric acid, hydroxy myristic acids such as 2-hydroxy myristic acid and 3-hydroxy myristic acid, hydroxy pentadecanoic acids such as 2-hydroxypentadecanoic acid and 3-hydroxypentadecanoic acid, hydroxy palmitic acids such as 2-hydroxy palmitic acid and 3-hydroxy palmitic acid, hydroxy stearic acids such as 2-hydroxystearic acid, 3-hydroxystearic acid and 12-hydroxystearic acid, hydroxy arachidic acids such as 2-hydroxy arachidic acid and 3-hydroxy arachidic acid, hydroxy behenic acids such as 2-hydroxy behenic acid and 3-hydroxy behenic acid, hydroxy lignoceric acids such as 2-hydroxy lignoceric acid and 3-hydroxy lignoceric acid, and self-condensation products thereof, castor oil derivatives such as castor oil fatty acids, hydrogenated castor oil fatty acids (hardened castor oil), dehydrated castor oil, dehydrated castor oil fatty acids, and self-condensation products thereof. The molecular weight of these fatty acid derivatives is preferably less than 5000 (more preferably 4000 or less, and even more preferably 3000 or less). The lower limit is preferably 200 or more (more preferably 250 or more, and even more preferably 300 or more). In the present invention, the molecular weight of the fatty acid derivative is a number average molecular weight (Mn), which is a so-called polystyrene equivalent molecular weight determined by gel permeation chromatography using a polystyrene polymer as a reference.

[0051] Examples of the carboxylic acid anhydride compound include anhydrides of the above carboxylic acid compounds, maleic anhydride, succinic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, pyromellitic anhydride, and trimellitic anhydride.

[0052] Examples of the copolymer having a carboxyl group include a styrene-maleic acid copolymer and a styrene-maleic anhydride copolymer.

[0053] In the present invention, it is preferable that compound (C) contains one or more selected from the group consisting of the above-mentioned phosphate ester compounds, the above-mentioned fatty acid derivatives, and the above-mentioned copolymers having a carboxyl group, and it is particularly preferable that compound (C) contains the above-mentioned phosphate ester compounds and / or the above-mentioned fatty acid derivatives. In addition, it is preferable that the fatty acid derivative includes one or more selected from castor oil derivatives (also simply referred to as "castor oil derivatives") such as castor oil fatty acid, hydrogenated castor oil fatty acid (hardened castor oil), dehydrated castor oil, dehydrated castor oil fatty acid, and self-condensation products thereof. In such a case, the pot life of the coating material can be sufficiently secured, and the effect of suppressing defects such as cracking and the adhesion when recoating (recoatability) can be improved.

[0054] The hydroxyl value of the compound (C) is preferably 0 to 100 mgKOH / g (more preferably 3 to 40 mgKOH / g, and even more preferably 5 to 30 mgKOH / g). Furthermore, it is suitable that the difference between the hydroxyl value of the compound (C) and the hydroxyl value of the polyol component (A) is preferably 80 mgKOH / g or less (preferably 50 mgKOH / g or less, and even more preferably 30 mgKOH / g or less). In such a case, the effect of the present invention can be enhanced without inhibiting the crosslinking reaction of the coating-forming component (A).

[0055] The mixing ratio of the compound (C) is 0.1 to 50 parts by mass (preferably 0.3 to 40 parts by mass, and more preferably 0.5 to 30 parts by mass) per 100 parts by mass of the solid content of the coating-forming component (A). In such a case, the effects of the present invention can be further enhanced.

[0056] In the present invention, in addition to the above components, it is preferable to contain a viscosity modifier (D). Examples of the viscosity modifier (D) include urea-based viscosity modifiers, fatty acid amide (amide)-based viscosity modifiers, polyacrylic-based viscosity modifiers, cellulose-based viscosity modifiers, and hydrogenated castor oil-based viscosity modifiers. These can be used alone or in combination of two or more. This can improve the coating workability and form a thick film.

[0057] In the present invention, it is particularly preferable that the viscosity modifier (D) contains at least one selected from fatty acid amide (amide)-based viscosity modifiers and hydrogenated castor oil-based viscosity modifiers (more preferably contains hydrogenated castor oil-based viscosity modifiers). In such a case, viscosity can be imparted stepwise without a sudden increase in viscosity during preparation of the coating material. As a result, even if a large amount of powder component (B) is contained, it becomes possible to mix sufficiently and obtain uniform dispersibility. In addition, the combined effect of the compound (C) ensures sufficient pot life of the coating material and imparts sufficient thixotropy to the coating material, so that the coating workability is further improved and a thick film can be formed without causing defects such as cracks.

[0058] Examples of hydrogenated castor oil viscosity modifiers include "Disparlon 305" and "Disparlon 4300" manufactured by Kusumoto Chemical Industries, Ltd., and "T-20SF" manufactured by Ito Oil Mills, Ltd. Examples of fatty acid amide (amide) viscosity modifiers include "Disparlon 6500" manufactured by Kusumoto Chemical Industries, Ltd., and "T-75F", "T-37F", "T-250", "T-550", and "T-850" manufactured by Ito Oil Mills, Ltd. In addition, "T-75F" and "T-37F" manufactured by Ito Oil Mills, Ltd. are mixtures of fatty acid amide and hydrogenated castor oil.

[0059] The acid value of the viscosity modifier (D) is preferably less than 10 mgKOH / g (more preferably 8 mgKOH / g or less) and is different from the compound (C) having the above acid value.

[0060] The mixing ratio of the viscosity modifier (D) is preferably 0.05 to 15 parts by mass (more preferably 0.1 to 10 parts by mass, and even more preferably 0.2 to 5 parts by mass) per 100 parts by mass of the solid content of the film-forming component (A). In such a case, the effects of the present invention can be further enhanced.

[0061] The coating material of the present invention may contain various additives as components other than those described above. Such additives may be any additives that do not significantly impair the effects of the present invention, and examples of such additives include wetting agents, plasticizers, lubricants, preservatives, antifungal agents, anti-algae agents, antibacterial agents, water absorbing agents, thickeners, leveling agents, dispersants, defoamers, crosslinking agents, silane coupling agents, ultraviolet absorbers, light stabilizers, antioxidants, halogen scavengers, diluting solvents, etc.

[0062] The heating residue of the coating material of the present invention is preferably 70 to 98 mass % (more preferably 75 to 95 mass %, and even more preferably 80 to 93 mass %). When the heating residue of the coating material satisfies the above range, excellent thick coating property and good coating workability can be obtained. The heating residue of the coating material is a value measured by the method of JIS K 5601-1-2, the heating temperature is 105°C, and the heating time is 60 minutes.

[0063] In the present invention, the viscosity of the coating material is preferably 5 to 70 Pa·s (more preferably 7 to 60 Pa·s, even more preferably 10 to 55 Pa·s, and particularly preferably 12 to 50 Pa·s). When the viscosity of the coating material satisfies the above range, the coating material has excellent workability and thick coating properties, and a uniform coating film can be formed. The viscosity of the coating material is the viscosity at 20 rpm (the guideline value at the fifth rotation) measured with a BH viscometer at a temperature of 25°C immediately after the coating material is prepared (after mixing the base agent and the curing agent in the case of a two-component type). The viscosity of the coating material can be adjusted by adding a diluting solvent according to the coating tool to be used, within the above viscosity range.

[0064] In the present invention, by applying a coating material that satisfies the above-mentioned ranges of heating residue and viscosity to form a coating, it is possible to further increase the thickness of the coating, and to stably form a uniform coating that exhibits good adhesion to the substrate.

[0065] The coating material of the present invention is preferably a multi-liquid type (e.g., two-liquid type, three-liquid type, etc.) coating material having a base agent containing the polyol component (A1) and a curing agent containing the polyisocyanate component (A2). That is, during distribution, the base agent and the curing agent are stored in separate packages, and are mixed when used (applied). In addition, the powder component (B), the compound (C), and the viscosity modifier (D) may be mixed into at least one of the base agent and the curing agent, but in the present invention, it is preferable to mix them into the base agent. Also, each component can be added when mixing the base agent and the curing agent.

[0066] The coating material of the present invention is preferably a multi-liquid coating material (e.g., a two-liquid coating material) having a base agent containing the polyol component (A1), the powder component (B), and the compound (C), and a curing agent containing the polyisocyanate component (A2). In this case, when the base agent and the curing agent are mixed, the action of the compound (C) can sufficiently ensure the pot life of the coating material, and can also improve the effect of suppressing defects such as cracking, and the adhesion when recoating (recoatability), etc.

[0067] Furthermore, the coating material of the present invention is preferably a multi-component coating material (e.g., a two-component coating material) having a base agent containing the polyol component (A1), the powder component (B), the compound (C), and the viscosity modifier (D), and a curing agent containing the polyisocyanate component (A2). In the present invention, the main component contains the compound (C) and the viscosity modifier (D) in combination, so that the viscosity can be gradually increased without a sudden increase in viscosity during the preparation of the main component. As a result, even if the powder component (B) is contained in a large amount, it is possible to mix it sufficiently and obtain uniform dispersion. In addition, the combined effect of the compound (C) ensures a sufficient pot life of the coating material and can impart sufficient thixotropy to the coating material, so that the coating workability is further improved and a thick film can be formed without causing defects such as cracks.

[0068] The coating material of the present invention is suitable as a coating material applied to the surface coating of structures such as buildings and civil engineering structures. Specifically, it can be applied to various substrates such as walls, pillars, floors, beams, roofs, stairs, ceilings, and doors. Applicable substrates include, for example, concrete, mortar, siding boards, extrusion molding boards, gypsum boards, perlite boards, bricks, plastics, wood, metals, steel frames (steel materials), glass, and porcelain tiles. These substrates may have a coating already formed on their surfaces, may have been subjected to some kind of surface treatment (rust prevention treatment, flame retardant treatment, etc.), or may have wallpaper attached thereto.

[0069] When applying (painting) the coating material of the present invention to a substrate, an application tool such as a spray, roller, brush, or trowel can be used.

[0070] When the coating material of the present invention is applied to a substrate, it may be applied by one or several steps by the above method, but it is preferable to apply so that the dry film thickness per step is preferably 400 μm or more (more preferably 500 to 8000 μm). The final coating thickness may be appropriately set depending on the desired functionality, application site, etc., but is preferably about 0.4 to 8 mm. In addition, the coating material of the present invention has excellent curing properties because it forms a coating by the reaction of the above component (A1) and the above component (A2), and the drying is preferably performed at room temperature, and the interval between the next step is preferably 5 hours or more (more preferably 10 hours or more and up to 30 days).

[0071] When applying the coating material of the present invention, if necessary, the substrate may be subjected to surface treatment or a primer may be applied before applying the coating material. This can improve adhesion to the substrate and corrosion resistance (rust resistance), etc. Surface treatment of the substrate may include, for example, surface treatment with a solvent or acid, scraping with a disk sander, wire foil, scraper, wire brush, sandpaper, etc.

[0072] As the undercoat material, for example, a sealer, a primer, a base conditioner, a surfacer, a putty, etc., as well as a flat-type paint can be applied. These may be either clear type or colored type. In addition, either water-based or solvent-based may be used, and can be appropriately selected according to the painting location, etc., and one or more types can be used. As the undercoat material, for example, it is preferable to contain a resin component such as an acrylic resin, a urethane resin, an epoxy resin, etc., and in addition to the above-mentioned resin components, various additives can be blended to an extent that does not affect the effect of the present invention. Examples of such additives include anti-rust pigments, extender pigments, coloring pigments, plasticizers, preservatives, anti-mold agents, anti-algae agents, defoamers, leveling agents, pigment dispersants, anti-settling agents, anti-sagging agents, antioxidants, catalysts, coupling agents, crosslinking agents, etc.

[0073] The undercoat material can be applied by various methods, such as brush coating, roller coating, spray coating, etc. The amount of application is preferably 30 to 500 g / m 2 (More preferably 50 to 300 g / m 2 The number of times the undercoat material is applied may be appropriately determined depending on the surface condition of the substrate, etc., but is preferably 1 to 2 times.

[0074] Furthermore, in the present invention, a finishing material layer can be laminated on the covering material layer (coating) formed by the above-mentioned covering material. Such a finishing material layer is not particularly limited, and a known finishing material can be laminated. Such a finishing material layer can be laminated by applying a topcoat material or by attaching various sheet materials, wooden boards (wooden surface materials), etc.

[0075] As the above-mentioned topcoat material, any of clear type or colored type, glossy type or matte type, hard type or elastic type, thin film type or thick film type can be used. In addition, it may be either water-based or solvent-based, and can be appropriately selected according to the desired purpose. In addition, it is preferable that the topcoat material of the present invention contains a resin component. Examples of the form of such a resin include solvent-soluble resin, non-water-dispersed resin, solventless resin, water-dispersed resin, water-soluble resin, etc. Examples of the type of resin include acrylic resin, urethane resin, epoxy resin, vinyl chloride resin, vinyl acetate resin, acrylic silicone resin, fluororesin, silicon resin, polyvinyl alcohol, cellulose derivatives, etc., or composites thereof. These can be used alone or in combination of two or more. In particular, in the present invention, it is preferable to include one or more selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin.

[0076] Furthermore, the resin component may have crosslinking reactivity. When the resin component is a crosslinking reactive resin, the water resistance, durability, and adhesion of the formed coating are improved, and the occurrence of swelling and peeling of the coating due to rainfall, condensation, etc. and the decrease in heat resistance can be suppressed. Such a crosslinking reactive resin may be either one that causes a crosslinking reaction by itself or one that causes a crosslinking reaction by a crosslinking agent that is mixed separately. Such crosslinking reactivity can be imparted by combining reactive functional groups such as, for example, a hydroxyl group and an isocyanate group, a carbonyl group and a hydrazide group, an epoxy group and an amino group, an aldo group and a semicarbazide group, a keto group and a semicarbazide group, alkoxyl groups, a carboxyl group and a metal ion, a carboxyl group and a carbodiimide group, a carboxyl group and an epoxy group, a carboxyl group and an aziridine group, or a carboxyl group and an oxazoline group. Among these, it is preferable to include one or more crosslinking reactive resins selected from a hydroxyl group-isocyanate group, a carbonyl group and a hydrazide group, and an epoxy group and an amino group.

[0077] As components other than the resin component of the above-mentioned topcoat material, for example, color pigments, extender pigments, aggregates, etc. can be mixed. By appropriately blending such components, it is possible to express the desired color and texture. The amount of color pigments, extender pigments, aggregates, etc. to be mixed is not particularly limited as long as it is within a range that does not inhibit the functionality (e.g., foamability, heat resistance protection, etc.) of the above-mentioned coating material, but is preferably 1 to 2000 parts by mass (more preferably 5 to 1000 parts by mass) relative to 100 parts by mass of the solid content of the resin component.

[0078] In the present invention, it is particularly preferable to use pigments having infrared reflectivity and / or infrared transmittance as the color pigments and extender pigments, which can further enhance the effects of heat resistance protection and the like.

[0079] Examples of pigments having infrared reflectivity include aluminum flakes, titanium oxide, barium sulfate, zinc oxide, iron oxide, calcium carbonate, silicon oxide, magnesium oxide, zirconium oxide, yttrium oxide, indium oxide, alumina, iron-chromium composite oxide, manganese-bismuth composite oxide, manganese-yttrium composite oxide, black iron oxide, iron-manganese composite oxide, iron-copper-manganese composite oxide, iron-chromium-cobalt composite oxide, copper-chromium composite oxide, copper-manganese-chromium composite oxide, and the like, and one or more of these can be used.

[0080] Examples of pigments having infrared transmittance include perylene pigments, azo pigments, yellow lead, titanium red, cadmium red, quinacridone red, isoindolinone, benzimidazolone, phthalocyanine green, phthalocyanine blue, cobalt blue, indanthrene blue, ultramarine, and Prussian blue, and one or more of these can be used.

[0081] Furthermore, the topcoat material can also contain various additives that can be used in normal paints. Examples of such additives include thickeners, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, defoamers, adsorbents, ultraviolet absorbers, light stabilizers, antioxidants, fibers, low-pollution agents, hydrophilizing agents, water repellents, coupling agents, catalysts, etc.

[0082] In the present invention, the topcoat material can be applied by repainting, or two or more types of topcoat materials can be laminated and applied. When two or more types of topcoat materials are laminated, it is preferable that the first topcoat material (intermediate coating material) contains one or more resin components selected from urethane resin, epoxy resin, acrylic resin, and acrylic silicone resin (particularly preferably, urethane resin, epoxy resin, etc.). This can further increase the adhesion between the layers of the coating material and the topcoat material. Furthermore, a topcoat material coating with excellent coating properties can be formed.

[0083] The topcoat material may be applied by a known application method, for example, by using various methods such as brush coating, roller coating, spray coating, etc. The amount of coating is preferably 30 to 5000 g / m 2 (More preferably 50 to 3000 g / m 2 The number of times the topcoat material is applied may be set appropriately depending on the surface condition of the substrate, but is preferably 1 to 2 times. Drying may be preferably performed at room temperature.

[0084] Examples of the sheet material include decorative films, decorative sheets, sheet building materials, wallpapers, etc. The thickness of the sheet material is preferably 0.01 to 30 mm (more preferably 0.05 to 20 mm). These may be attached via a known adhesive (pressure-sensitive adhesive) or the like. EXAMPLES

[0085] The following examples will clarify the features of the present invention, but the present invention is not limited to these examples.

[0086] The following raw materials were used:

[0087] <Polyol component (A1)> (A1) Polyether polyol (addition polymer of ethylene oxide and propylene oxide using glycerin as an initiator, number average molecular weight 7000, number of functional groups 3, hydroxyl value 24 mg KOH / g, terminal ethylene oxide addition, solid content 100% by mass) <Polyisocyanate component (A2)> (A2) Biuret type hexamethylene diisocyanate (NCO content 23.5%, solid content 100% by mass)

[0088] <Powder component (B)> (B1) Titanium oxide (B2) Ground calcium carbonate (B3) Melamine-coated ammonium polyphosphate (B4) Melamine (B5) Pentaerythritol

[0089] <Compound (C)> (C1) Phosphate ester compound of polyester / polyether polymer (acid value: 53 mg KOH / g) (C2) Palmitic acid (acid value: 220 mg KOH / g, number average molecular weight: 256) (C3) Dehydrated castor oil fatty acid (octadecadienoic acid) (acid value: 198 mg KOH / g, number average molecular weight: 280) (C4) Self-condensation product of castor oil fatty acid (acid value: 100 mg KOH / g, hydroxyl value: 80 mg KOH / g, number average molecular weight: 500) (C5) Self-condensation product of castor oil fatty acid (acid value: 46 mg KOH / g, hydroxyl value: 26 mg KOH / g, number average molecular weight: 1000) (C6) Self-condensation product of castor oil fatty acid (acid value: 30 mg KOH / g, hydroxyl value: 10 mg KOH / g, number average molecular weight: 2000) (C7) Self-condensation product of hydrogenated castor oil fatty acid (acid value: 34 mg KOH / g, hydroxyl value: 7 mg KOH / g, number average molecular weight: 1500) (C8) Styrene-maleic anhydride copolymer (acid value: 285 mg KOH / g, number average molecular weight: 9500) (C9) Styrene-maleic anhydride copolymer (acid value: 480 mg KOH / g, number average molecular weight: 5500)

[0090] <Viscosity adjuster (D)> (D1) Hydrogenated castor oil-based viscosity modifier (acid value: 1.2 mg KOH / g, solid content 100% by mass) (D2) Hydrogenated castor oil, fatty acid amide mixed viscosity modifier (acid value: 2.5 mg KOH / g, solid content 100% by mass) (D3) Fatty acid amide mixed viscosity modifier (acid value: 4.5 mg KOH / g, solid content 100% by mass) (D4) Urea-based viscosity modifier (solid content 50% by mass, medium: amide-based solvent) <Curing catalyst (P)> (P1) Dibutyltin dilaurate (active ingredient (purity): 97% by mass) <Other> (Additives) Dispersants, defoamers, plasticizers, diluting solvents, etc.

[0091] (Examples 1 to 16, Comparative Examples 1 to 2) According to the formulations shown in Tables 1 and 2, the (A1) component, the (B) component, the (C) component, the (D) component, the (P) component, and additives 1 and 2 were mixed in a conventional manner to prepare the main material. At this time, each of the constituent components could be mixed sufficiently, and the dispersibility of the (B) component could be ensured. In particular, in Examples 13 to 16, good viscosity could be imparted, and the (B) component could be mixed sufficiently. Furthermore, in Examples 13 to 15 (particularly Examples 13 to 14), viscosity could be imparted stepwise without a sudden increase in viscosity, and the main material could be efficiently prepared. Next, component (A2) was mixed as a curing agent under the following conditions to prepare a coating material, which was then evaluated as follows: The viscosity of the coating material when it was prepared (immediately after mixing the base agent and curing agent) was 18-25 Pa s. (Preparation of coating material) [I] Normal temperature (25℃, 60%Rh) [II] High temperature and high humidity (35℃, 90%Rh)

[0092] <Pot life evaluation> The prepared coating material was left to stand in the same environment and the viscosity was measured using a B-type viscometer (single cylindrical rotational viscometer). The evaluation criteria were the time it took for the viscosity to reach 40 Pa s, which is an indicator of the deterioration of spray paintability, and a four-level evaluation (A>B>C>D: poor). A: More than 6 hours B: 4 hours or more C: More than 2 hours D: Less than 2 hours

[0093] <Thickening evaluation 1> The test specimen was prepared by spraying (one coat) the coating material onto the entire inside surface (concave) of an L-shaped (equal-legged) steel plate (thickness 1.6 mm x outer dimensions A 150 mm x outer dimensions B 150 mm) that had previously been painted with an anti-rust coating, so that the dry film thickness was 3 mm under the following coating environment, and then curing (24 hours, 7 days). Coating environment (application and curing conditions) [I] Normal temperature (25℃, 60%Rh) [II] High temperature and high humidity (35℃, 90%Rh) The condition of the formed coating was visually inspected and evaluated on a four-level scale (A>B>C>D: poor), with a uniform coating being rated as "A" and cracks appearing in the coating at corners and other locations being rated as "D."

[0094] <Thickening evaluation 2> The coating material was sprayed onto the entire surface of a steel plate (150 mm long x 70 mm wide x 1.6 mm thick) that had previously been painted with an anti-rust coating, under the painting environment described below, so that the dry film thickness was 1.5 mm. After curing (process interval described below), the same coating material was sprayed onto the entire surface of the plate so that the dry film thickness was 1.5 mm, and the plate was then cured (24 hours, 7 days) to prepare the test specimen. ·Painting environment (painting and curing conditions) [I] Room temperature (25℃, 60%Rh, process interval 16 hours) [II] Under high temperature and high humidity (35℃, 90%Rh, process interval 16 hours) After 7 days of curing, cross-cuts were made in the coating of the test specimen with a utility knife, and tape was applied to the cross-cut areas and then peeled off to evaluate adhesion. The evaluation criteria were a four-level evaluation (A>B>C>D: poor), with "A" being no abnormality and "D" being peeled off between layers.

[0095] [Table 1]

[0096] [Table 2]

[0097] In Examples 1 to 16, a sufficient pot life was ensured, and a thick film could be formed without cracking, etc. On the other hand, in Comparative Example 1, a sufficient pot life was not obtained under high temperature and high humidity conditions, and in Comparative Example 2, a thick film could not be formed.

Claims

1. A coating material comprising a coating-forming component (A) and a powder component (B), The film-forming component (A) includes a polyol component (A1) and a polyisocyanate component (A2), The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The coating material further comprises a compound (C) having an acid value of 10 to 1000 mgKOH / g.

2. A multi-component coating material comprising a base material containing a polyol component (A1) and a powder component (B), and a curing agent containing a polyisocyanate component (A2), The polyol component (A1) and the polyisocyanate component (A2) are a film-forming component (A), The powder component (B) is contained in an amount of 100 parts by mass or more per 100 parts by mass of the solid content of the coating-forming component (A), The base material comprises a compound (C) having an acid value of 10 to 1000 mgKOH / g.

Citation Information

Patent Citations

  • Two-pack coating composition

    JP2000109753A